Provisioning Quality of Service of Wireless Telemedicine for E-health Services - -, Mustafa Almahdi Algaet; Muhamad Noh, Zul Azri; Shibghatullah, Abdul Samad; -, Ali Ahmad Milad (2013)
Telemedicine is not yet all worked out where it can be utilized constantly or flexibly. But, it has enormous potential to be a tremendous asset to the world and all its civilizations. Telemedicine has had a positive impact on some aspects of patient care. There is no arguing that the contributions it can make have endless possibilities however more time and effort will be needed to organize telemedicine for it to be confidently accepted. Asynchronous telemedicine does not require the simultaneous availability of the source and recipient of patient information. Telemedicine can be roughly characterized as either synchronous or asynchronous. Synchronous telemedicine involves caregivers acquiring and acting upon information about a remote patient in near real-time.